Pattern and determinants of unintentional injuries in children (<18 years) from rural puducherry: A cross-sectional analytical study - Burhana Begom Choudhury; S. Ganesh Kumar; Henna K (Clinical Epidemiology and Global Health)
Background: Unintentional injuries (UI) among <18 years contributes to a significant public health problem due to their physical and psychological makeup. This study estimated the occurrence of unintentional injuries (UI) and identifies the factors associated with common unintentional injuries among children below 18 years residing in rural areas of Puducherry, India. Method: This cross-sectional study included 596 children below 18 years who are living in the study area. Falls, road traffic injuries, burns, near drowning, poisonings and other injuries reported by participant or care-giver that had happened in last one year or in their entire life time which can be recalled was considered as unintentional Injuries. A pre-tested structured questionnaire was used to collect data regarding injuries. Simple descriptive analysis and the Chi-square test were incorporated in statistical analysis. In order to understand the factors associated with UI, log binomial regression model was performed. Results: The prevalence of UI was found to be 32.6 % (95 %CI: 28.9–36.4) among 596 study participants. The common types of UI reported were accidental falls (34 %), traffic related injuries (20.6 %) and animal bites (17.5 %). It revealed that the socio-demographic characteristics of the study participants were significantly associated with the occurrence of UI such as gender and age of child, educational status of the child and primary caregiver, socio-economic status from which the child belongs to, age of the primary caregiver. Discussion: The study highlights the importance for creating awareness about injury prevention strategies and developing policies to lower the burden of UI in children.